Guidance Book Layanan Employee Care Center (ECC) di Instansi X Guna Meningkatkan Kesejahteraan Karyawan - Aurellia Indah Pramesti; Lintang Alisya Ramadhani; Rezky Moudya Muis; Azizah Aulia; Muhammad Ramadhan; Rostiana Rostiana (Departement of Mathematics Education, 2022)
Several factors can influence the realization of quality human resources, namely by paying attention to welfare, communication and work facilities. One of the facilities in Agency X to improve employee welfare is by providing Employee Care Center (ECC) services. The purpose of the establishment of the Employee Care Center (ECC) is to improve the psychological well-being, performance and productivity of employees and to maintain a balance between personal and work life. Some of the services available at the Employee Care Center (ECC) include counseling, psychological education, psychological assistance, advisory teams on matters of marriage and divorce and special treatment. To provide counseling services, there are three channels that can be carried out by employees, namely self-referral by coming directly to the Employee Care Center (ECC) room, self-referral through e-counseling, and referrals to superiors or work units. The results of implementing the Employee Care Center (ECC) program service guidance book are to be used in the Employee Care Center (ECC) socialization activities at the head office and all representative offices of Agency X in order to introduce the Employee Care Center (ECC) service to all bureaus and work units in in Agency X, and it is also hoped that with this guidance book, employees at Agency X can use the Employee Care Center (ECC) service to assist in resolving problems that occur and can improve welfare and productivity at work.